Garcinia atroviridis fruit extract alters lipid accumulation in 3T3-L1 cell line model - Hamidon, Hanisuhana; Bakhtiar, M. Taher; Darnis, Deny Susanti; Ahmad Rusmili, Muhamad Rusdi (2017)
Obesity is accumulation of excess body fat to the extent it may have an adverse effect on health. It is undeniably a complex disease with risk factors combination of genetics, lifestyle, nutrition, increasing age and lack of physical activity. Alarming increase of obesity prevalence since past few years brings the concern to explore effective therapy against obesity. Thus, targeting preadipocyte differentiation (adipogenesis) is one of natural product’s approaches to exert its anti-obesity property. The success of other Garcinia species for obesity management opened the gap to study the lipid alteration potential the locally underexplored Garcinia atroviridis or Asam Gelugur on 3T3-L1 cell culture model. The fresh fruit was extracted and freeze-dried. We first found that the powdered extract did not affect cell viability of both preadipocyte and adipocyte cells. The extract significantly inhibited adipogenesis by decreasing intracellular lipid accumulation as analysed qualitatively and quantitatively using Oil Red O stain. We further investigated the inhibition effect by means of quantifying the protein associated with adipogenesis, PPARγ and C/EBPα. The treatment only affects the expression of C/EBPα protein significantly. Furthermore, the extract was also enhanced the adipocytes breakdown (adipolysis) as revealed by glycerol concentration measured. Taken together, our findings indicated that the fruit extract of G. atroviridis plays a role in alteration of lipid accumulation with the intervention of protein associated with adipogenesis. Understanding adipogenesis and its molecular mechanisms may provide clues for future strategies development in preventing and treating obesity.